ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT EFISIENSI PERBANKAN SYARIAH DI INDONESIA - Permana, Fafa Yushifa; Adityawarman, Adityawarman (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to examine efficiencies of Islamic banking in Indonesia as well as examine the factor that affect the level of efficiency of Islamic banking in Indonesia especially cost efficiency. Efficiency score then made as  dependent variable was obtained using Data Envelopment Analysis   (DEA)   method.   Then   the   independent  variables   are   using   size   of   banking,   ROA, capitalization, loan quality and bank expenses to analysis the factors that influencing the efficiency of Islamic banking in Indonesia.The population in this study is used throughout the Islamic banking in Indonesia. They are 11 Islamic banking in the 4 years of this study, which is means there are 44 samples used as objects in this study. Data collection method that are used in this study is documentation with using annual reports each  Islamic  banking  between  2010  to 2013.  Regression  analysis  was  used as a method  of data analysis in this research.The results showed that from 44 samples contained only 16 samples can be efficiency. And from  regression  analysis,  find that  ROA  is positively  and significantly  associated  to Efficiency  of Islamic banking in Indonesia